Managing Hypothermia in Emergency Exploratory Laparatomy: A Case Report - Wulandari, Putu Aditya Ika; Raya, Nyoman Agus Jagat (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: The writing of this case report aims to analyze the management of hypothermia in patients undergoing emergency laparotomy in the operating room. Methods: This research method is a case report study with a retrospective approach by monitoring, interviewing, and using medical data of patients undergoing emergency exploratory laparotomy surgery in the Emergency Operating Room of Prof. Dr. I.G.N.G. Ngoerah Hospital. The data collected were the patient's disease course, diagnosis, actions, and nursing interventions. Results: In both cases, the temperature was maintained between 35.5°C to 36°C using a combination of warm blankets, mattresses, and warmed NaCl. Conclusion: This case report concludes that providing warm blankets, warm mattresses, and warm NaCl to wash the abdomen is beneficial in preventing perioperative hypothermia in patients undergoing emergency exploratory laparotomy. The operating room nurse is expected always to monitor the patient's temperature so as not to experience hypothermia.